Opportunities and Challenges for the Adult Learner in the 21st Century: A Case Study of One Tertiary Education Institution in Zimbabwe - Moyo Mlungisi; Nyathi Vuyiswa Sandra (Randwick International of Education and Linguistics Science Journal, 2020)
Quality education in Zimbabwe has remained one of the major demands in the system. This has therefore seen the majority of both academic and non-academic staff in institutions of higher learning advancing themselves in various courses and programmes. This study hence was conducted to explore opportunities and challenges experienced by adult individuals as they further pursue their studies. It was a case study of one tertiary education institution conducted within the framework of a qualitative research paradigm and also influenced by the human capital theory. Semi structured questionnaires and interviews were used to generate data from 20 participants that were purposively and conveniently targeted for the study. The major findings revealed that staff in tertiary institutions envy to advance themselves education wise. However, their efforts are being derailed by several challenges which unfold themselves socially, academically and economically, among others. The results further revealed that issues of institutions policy on manpower development were a cause of concern. Ultimately the study concluded that continued adult education in the 21st century is quite pivotal despite the challenges that these adults encounter. Recommendations put forth in the study, therefore include reconceptualization of institution policy on manpower development, availing financial resources and a variety of schemes for adult education